THE WHEEL: SHOULD WE REINVENT IT? - Norton, Hannah (American Economic Review, 1974)
This paper begins with the premise that our intercity passenger transport system is less effective than we would like, and it asks if there is a place for revitalized railroad passenger service. The railroad passenger efforts of the thirties and of the early fifties were doomed at the outset by public policy favoring airport and highway development. Energy and environment may be factors, but service must be made attractive. The paper concludes that the railroad role is in the 500 to 1000 mile range between heavily populated areas where congestion is severe. It concludes that such service can be made equal to airline and bus service.